Stating the Sacred Religion, China, and the Formation of the Nation-State - Walsh, Michael J. 1968- (New York Columbia University Press, 2020)
Intro -- Table of Contents -- Preface -- 1. Territory -- 2. Constitution -- 3. Religion -- 4. Reincarnation -- 5. Contact -- 6. Nativity -- Glossary -- Notes -- Bibliography -- Index.
Stating the Sacred offers a novel approach to nation-state formation, arguing that its most critical element is how the state sacralizes the nation. Focusing primarily on China, Michael J. Walsh argues that the foundational role of the sacred makes all nation-states religious states
Keywords: Civil religion-China; Electronic books